Tecendo Diálogos Entre Funcionalismo E Dialogismo Para Análise De Fenômenos Em Processo De Variação/Mudança (PERcursos Linguísticos, 2022)
This text aims to argue that the assemblage of a form/function in the effective use of language occurs within the scope of genres of the discourse. Using an interpretive nature, this research is bibliographical, based on autor (2017), who has proposed a dialogue between the functionalist fields, considering both the West Coast (HOPPER; TRAUGOTT, 1993; 2003; GIVÓN, 2001; TRAUGOTT, 2001, among others) and the dialogic perspectives (BAKHTIN, 2014 [1924]; BAKHTIN [VOLOCHÍNOV], 2014 [1929]; MEDVIÉDV, 2012 [1928], among others), for the treatment of phenomena in variation/change, taking the case of the expression of the future of the present in Portuguese from Brazil as an example. The research results point to the relevance of considering: (i) that the expression of the future of the present is a representation constructed in/by the discourse; (ii) that chronotopic and evaluative relationships are constitutive of all linguistic uses; (iii) that linguistic resources such as variables, on the one hand, and multifunctional ones, on the other hand, being arranged to fulfill a teleological function, are not always the same, being, therefore, relevant to the study of stylistic variation; (iii) that style pertains to the discourse around genres, hence the argument that it is within the scope of the genres that the explanation of the form/function relationship must be sought.